Sustainable Innovation Management Model (Mgi) for Agro-Industrial Citrus Chain - Gonzalez-Candia, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This paper proposes a sustainable innovation management model (hereinafter MGI) aimed at enhancing sustainability and leveraging open innovation opportunities within the Citrus agro-industrial chain in the Quindío Department, Colombia. The methodology combines surveys, consensus percentages, relevance and congruence indices, and a review of the literature from the last ten years, particularly in the Google Scholar and Scopus databases. A total of 97 documents directly related to innovation management in the citrus sector were reviewed, along with 58 indirect references. Through three questionnaires, 120 variables were identified, categorized into input (53), transformation (36), and output (31) stages. The findings, supported by sector analysis and foresight studies conducted for six regional agro-industrial chains, led to the development of three potential MGI models, one of which was selected for further application. The study highlights several challenges within the citrus value chain, including weak leadership, limited market competitiveness, outdated organizational structures, slow adoption of advanced technologies, and inadequate investment. The proposed MGI, with a focus on sustainable innovation, offers a generic interactive model that presents a dynamic and adaptable solution to drive competitiveness and value creation in the citrus sector. The chain studied requires not only the participation of different interest groups, but also the application of artificial intelligence to close the gaps and allow for sustainable innovation to be generated of sustainable innovation. © 2025 by the authors.